2016
DOI: 10.3892/mmr.2016.5116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Per2 overexpression on growth inhibition and metastasis, and on MTA1, nm23-H1 and the autophagy-associated PI3K/PKB signaling pathway in nude mice xenograft models of ovarian cancer

Abstract: The aim of the present study was to evaluate the association between Period2 (Per2) and the occurrence and development of ovarian cancer, in addition to evaluating the effect of this gene on the growth and metastasis of ovarian cancer in nude mice xenograft models. The detection of Per2 by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting methods at various stages of ovarian cancer in tumor tissue samples was conducted. Nude mice xenograft models of ovarian cancer were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Conversely, after upregulating PER2, PI3K/AKT/mTOR pathway activity was reduced, thereby promoting apoptosis (43). Wang et al injected a recombinant PER2 plasmid to induce PER2 overexpression in an allograft ovarian cancer nude mouse model, revealing that PIK3CA and AKT protein expression levels could be reduced as a result (44). The present study also indicated that PER2 expression in clinical specimens of OSCC was negatively correlated with PIK3CA expression, but positively correlated with PTEN expression.…”
Section: Per2 Expressionsupporting
confidence: 64%
“…Conversely, after upregulating PER2, PI3K/AKT/mTOR pathway activity was reduced, thereby promoting apoptosis (43). Wang et al injected a recombinant PER2 plasmid to induce PER2 overexpression in an allograft ovarian cancer nude mouse model, revealing that PIK3CA and AKT protein expression levels could be reduced as a result (44). The present study also indicated that PER2 expression in clinical specimens of OSCC was negatively correlated with PIK3CA expression, but positively correlated with PTEN expression.…”
Section: Per2 Expressionsupporting
confidence: 64%
“…Previous studies have suggested that the PER gene family plays a role in the regulation of cell physiological processes, such as the cell cycle [6], DNA damage response [6,7], cell proliferation, and apoptosis [8]. Abnormal expression of the PER genes has been demonstrated to be associated with the occurrence and development of cancer [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A disorder of the circadian rhythm caused by shift-work is closely related to the formation and development of ovarian tumors [ 26 ]. A gene associated with the biological clock, Per2 , can inhibit the growth and metastasis of ovarian cancer cells [ 27 ]. Whether an abnormal circadian rhythm influences the chemotherapy effect and prognosis of patients with ovarian cancer has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%